Macronutrient malabsorption in acute diarrhea: Prevalence and affecting factors - Lilis D. Hendrawati; Agus Firmansyah; Darlan Darwis (Paediatrica Indonesiana, 2005)
Introduction Diarrhea remains a major problem for communityhealth in Indonesia. More than 25% of children with severe diar-rhea suffer from malabsorption syndrome.Objectives This study aimed to determine the age range of chil-dren with acute diarrhea, the prevalence of macronutrient malab-sorption, and the relationship between age and bacterial infec-tion in macronutrient malabsorption.Methods This was a cross-sectional study, subjects were chil-dren aged 0-59 months with acute diarrhea whose stools wereobtained and examined in the laboratory of GastrohepatologyDivision, Department of Child Health, Cipto Mangunkusumo Hospi-tal, Jakarta from January 2002 to December 2003.Results Children with acute diarrhea were mostly in the agerange of 0-11 months (61%). The prevalence of lactose malab-sorption was 11%, carbohydrate malabsorption was 19%, andfat malabsorption was 51%. Moreover, the age group of 0-11months had a 1.5 times greater possibility of lactose and fatmalabsorption compared to that of 12-59 months. The 12-59 monthsage group had a greater possibility of suffering carbohydratemaldigestion (70%). The group of children who did not sufferfrom bacterial infection had a higher prevalence of lactose mal-absorption (54%), carbohydrate maldigestion (65%), and fatmalabsorption (58%).Conclusions Acute diarrhea occurred more frequently in theage of 0-11 months. There was a significant correlation betweenthe age groups of 0-11 months and 12-59 months in experiencingmacronutrient malabsorption. Lactose malabsorption, carbohy-drate maldigestion, and fat malabsorption were encountered morefrequently in the group that did not have bacterial infection